Factores de riesgo cardiovascular y condiciones socioeconómicas y sociodemográficas en México, 2000 - 2018 - Daniel Lozano Keymolen; Sergio Cuauhtémoc Gaxiola Robles Linares (Población y Salud en Mesoamérica)
Introduction: In high-income countries, socioeconomic status is related to differences in the prevalence and incidence of cardiovascular risk factors. In middle-income countries like Mexico, the evidence is less so the objective of the study was to estimate the trends in the prevalences of six of the main modifiable cardiovascular risk factors: diabetes, hypertension, high cholesterol, tobacco use, alcohol use, and obesity, according to the level of socioeconomic conditions at home among adults 20 years of age and over in the period 2000 - 2018. Method: The data were obtained from four nationally representative cross-sectional health surveys. With individual samples from each survey, the prevalences of cardiovascular risk factors were estimated. With a cluster analysis, three levels of socioeconomic conditions were determined. In each sample, with logistic regressions, the prevalences of each risk factor were estimated according to the socioeconomic level determined by each cluster, adjusting for sex, age, and education. Results: Unlike diabetes, hypertension, cholesterol or obesity, tobacco and alcohol consumption have decreased. Obesity, arterial hypertension, tobacco or alcohol consumption and high cholesterol showed differences between the high and low levels of socioeconomic conditions in the four points analyzed, but not diabetes. Conclusion: Programs and policies focused on the modification, care and medical treatment of cardiovascular risk factors should be consolidated.